Muscle repair and complications of muscle healing: radiological imaging - Slavotinek, J. (Medicine and Science in Tennis, 2007)
Muscle injury is one of the most common musculoskeletal injuries and typically occurs at or close to the musculotendinous junction or epimysium. Although aspects of clinical and radiological diagnosis are well documented, less attention has been directed to the potential role of imaging during the process of muscle repair and the complications that may develop following muscle injury.